The English language level of proficiency on mathematical problem solving skills - Mohammad Abuqutaish, Reem Hisham; Al-Zayed, Norma (Opción, 2020)
This study aimed to examine the effect of the students’ level of proficiency in the English language on their mathematical problem solving skills, and how the instructional design for mathematical problem solving may be altered to meet the individual students’ needs. The findings revealed that the students’ level of proficiency in the English Language, the language of instruction, directly affected the students’ performance in the mathematical problem solving test. The participants in the advanced group obtained higher means and percentages of correct answers across the different categories of the mathematical problem solving test.